2020
DOI: 10.1186/s12884-020-02876-1
|View full text |Cite
|
Sign up to set email alerts
|

Is perinatal asphyxia predictable?

Abstract: Background: The objective of our study was to evaluate the association between perinatal asphyxia and hypoxicischemic encephalopathy (HIE) with the presence of ante and intrapartum risk factors and/or abnormal fetal heart rate (FHR) findings, in order to improve maternal and neonatal management. Methods: We did a prospective observational cohort study from a network of four hospitals (one Hub center with neonatal intensive care unit and three level I Spoke centers) between 2014 and 2016. Neonates of gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
1
25
2
14
Order By: Relevance
“…Locatelli et al indicated the contribution of nulliparity to the development of perinatal asphyxia by the higher incidence of pregnancy complications associated with it, including defective placentation and impaired fetal growth. Also, they reported that due to the longer duration of labor, nulliparous women are at higher risk of infection and fetal intolerance to labor, surgical interventions, and related perinatal incidents 18 . However, Liljestrom et al stated that obstetric emergencies are more common in the multiparous women than in the nulliparous women among HIE cases, illustrating a major problem in the labor process 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Locatelli et al indicated the contribution of nulliparity to the development of perinatal asphyxia by the higher incidence of pregnancy complications associated with it, including defective placentation and impaired fetal growth. Also, they reported that due to the longer duration of labor, nulliparous women are at higher risk of infection and fetal intolerance to labor, surgical interventions, and related perinatal incidents 18 . However, Liljestrom et al stated that obstetric emergencies are more common in the multiparous women than in the nulliparous women among HIE cases, illustrating a major problem in the labor process 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, they reported that due to the longer duration of labor, nulliparous women are at higher risk of infection and fetal intolerance to labor, surgical interventions, and related perinatal incidents. 18 However, Liljestrom et al stated that obstetric emergencies are more common in the multiparous women than in the nulliparous women among HIE cases, illustrating a major problem in the labor process. 35 In our study, as mentioned in previous studies, nulliparity was more prevalent in the birth asphyxia group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HRV entropy indexes seem to be appropriate to describe neonatal seizures with a specific etiology such as the hypoxic-ischemic encephalopathies or, in general, with asphyxia episodes [ 56 , 57 ]. Moreover, cardio-regulatory system differences from a newborn with seizures from a seizure-free one might also be present during interictal activity rather than only during or close to an ictal event.…”
Section: Discussionmentioning
confidence: 99%